The Influence of Leadership Effectiveness, Adversity Quotient, and Organizational Culture on Teacher’s Performance - Sulastry, Heny; Harapan, Edi; Rahman, Andi (Journal of Social Work and Science Education, 2023)
This study determined (1) the effect of principal’s leadership effectiveness on teacher’s performance, (2) the effect of adversity quotient on teacher’s performance, (3) the influence of organizational culture on teacher’s performance, and (4) the effect of the effectiveness leadership, adversity quotient, and organizational culture on the performance of high school teachers in Pulau Rimau District, Banyuasin Regency. The sample in this study were 101 teachers who teach in all high school/MA level in Pulau Rimau District. The technique of collecting data is using questionnaire. Data analysis techniques using inferential statistics, simple linear regression test and multiple linear regression test. The results of this study indicate that the results of multiple linear regression hypothesis testing between leadership effectiveness variables (X1), adversity quotient (X2) and organizational culture (X3) on the teacher’s performance (Y) the value of the regression equation constant is 28.622 and the coefficient value of the independent variable b1 is 0.207, b2 is 0.215 and b3 is 0.561. This means that the effectiveness of leadership, adversity quotient and organizational culture has increased significantly on teacher’s performance.